2013
DOI: 10.1089/lap.2013.0030
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Barbed Suture for Gastrointestinal Suture: A Prospective and Randomized Study on Obese Patients Undergoing Gastric Bypass

Abstract: Our study appears to be encouraging to suggest the use of barbed suture for gastrointestinal anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 22 publications
1
43
1
4
Order By: Relevance
“…Most of the published articles over recent years are related to bariatric surgery and barbed sutures' use in the performance of laparoscopic gastric bypass [34][35][36][37][38][39][40]. It is well known that performing intracorporeal anastomosis (suture and knottying) requires specific training and a learning curve in every surgeon.…”
Section: Use Of Barbed Sutures In Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the published articles over recent years are related to bariatric surgery and barbed sutures' use in the performance of laparoscopic gastric bypass [34][35][36][37][38][39][40]. It is well known that performing intracorporeal anastomosis (suture and knottying) requires specific training and a learning curve in every surgeon.…”
Section: Use Of Barbed Sutures In Bariatric Surgerymentioning
confidence: 99%
“…In this way, Milone et al [34] reported the first prospective randomized controlled study evaluating the efficacy of V-Loc suture on gastrojejunal anastomosis in human subjects undergoing gastric bypass. They included 60 patients in the study, in which barbed sutures were used in 30 patients while poliglactin 3-0 was used in the other 30.…”
Section: Use Of Barbed Sutures In Bariatric Surgerymentioning
confidence: 99%
“…To date, the efficacy of this new material has been evaluated in different surgical fields, a few general surgery studies are available [12][13][14][15][16][17][18], gynecologists have also demonstrated its utilities [19][20][21], oncologists have reported advantages in its properties [22] and urology is the field where its usefulness is already a standard and concentrates most of its reports [23][24][25][26][27].…”
mentioning
confidence: 99%
“…This should permit a greater distribution of tensile strength along the wound and increase the surface area of adhesion between the tissues. Consequently, the knotless, unidirectional barbed suture reduced the time required to close the entry hole compared with conventional surgical suture with intracorporeal knots (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…We previously described our technique and initial experience from intracorporeal staple-conserving, deltashaped gastroduodenostomy after distal gastrectomy in 2011, including the first use of barbed sutures for gastrointestinal suturing (20). There are some reports on the use of barbed sutures in digestive surgery to date, but there have been no prospective reports of bowel anastomosis in laparoscopic gastric surgery for malignant disease (21)(22)(23)(24).…”
mentioning
confidence: 99%